If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-1)=2(3x+5)
We move all terms to the left:
2(x-1)-(2(3x+5))=0
We multiply parentheses
2x-(2(3x+5))-2=0
We calculate terms in parentheses: -(2(3x+5)), so:We get rid of parentheses
2(3x+5)
We multiply parentheses
6x+10
Back to the equation:
-(6x+10)
2x-6x-10-2=0
We add all the numbers together, and all the variables
-4x-12=0
We move all terms containing x to the left, all other terms to the right
-4x=12
x=12/-4
x=-3
| y=2/2-4 | | F(x)=2x³-3x²+8 | | y=2/1-4 | | 4x+6+2x+15+87=180 | | 4x+6+2x+15=87 | | (5w=1)-(3w=4)= | | Tx9=117 | | 24=8-4y | | 12x=12=48 | | 40=20x+260 | | {x}{8}=5 | | 20.42x=5.16x | | (x^2)+3x+2=90 | | 4(m+7)=2(8m-40) | | 5(v+3)-8v=30 | | 4x-17=49.4 | | 9-x2=18 | | 9x=75; | | 9x=75;x=8.3 | | -6x+4(x-7)=10 | | 4x-4+2(x-5)=9x+8-2x | | d/5+20=25 | | 15x-167=9x-257 | | 6x+4+15–7xx=19 | | 20x+(-3)=-9x+5 | | 5y2–3y2= | | 19x+125=11x+221 | | -0.5x=-4.38 | | 5(y+7)-7y=33 | | 110=x+116 | | 2x+12=x+21 | | 104=x+128 |